Transitioning from Androcentrism towards a New Approach to Mainstreaming Gender Perspective Through the Inter-American Court - Estrada Vargas, Eduardo A (2024)
The primary goal of this research is to introduce a new approach to mainstreaming gender perspective, which includes not only women and girls but also the lesbian, gay, bisexual, transgender, and intersex (LGBTI) population. The study begins by examining the androcentric view of society, which has fostered its heteronormativity and patriarchal system. It then explores the evolution of the concepts of gender perspective and gender identity. Finally, the analysis evaluates judgments and advisory opinions issued by the Inter-American Court of Human Rights (IACHR) on matters concerning non-discrimination, sexual orientation, family, work, and equal protection under the law. These legal decisions establish reparative actions to safeguard and advance the rights of vulnerable groups. The study also aims to underscore the reparative measures concerning non-repetition guarantees, which the Inter-American Court advocates to promote mechanisms and public policies that States must adopt to overcome barriers of discrimination and social stigma that continue to impact Latin American societies.